The Effect of Educandy-Based Gamified Learning Media on Students’ Learning Outcomes in Islamic Education: A Pre-Experimental Study in Vocational High School - Anggraini, Cici; Alfurqan (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2026)
This study aims to examine the effect of Educandy-based gamified learning media on students’ learning outcomes in Islamic Religious Education (PAI) at the vocational high school level. Employing a quantitative approach with a pre-experimental one-group pretest–posttest design, the study involved 32 tenth-grade students at SMK Pertanian Pembangunan Negeri Padang. Data were collected using a 30-item multiple-choice test that had been validated and tested for reliability, along with observation sheets to assess affective and psychomotor domains. Data analysis was conducted using descriptive statistics, Shapiro–Wilk normality test, paired sample t-test, normalized gain (N-Gain), and effect size (Cohen’s d). The findings reveal a substantial increase in students’ mean scores from 61.09 in the pretest to 83.56 in the posttest, with a statistically significant difference (p < 0.05). The N-Gain value of 0.58 indicates a moderate level of improvement, while the effect size of 1.54 reflects a strong practical impact. In addition, observational data show that students achieved very good performance in both affective and psychomotor domains. The novelty of this study lies in its integration of gamification-based learning with a multidimensional assessment of learning outcomes (covering cognitive, affective, and psychomotor aspects) within the context of Islamic Religious Education, particularly in vocational schools where such approaches remain underexplored. Unlike prior studies that predominantly focus on cognitive achievement or motivation, this research provides a more holistic evaluation of learning effectiveness. The study contributes both theoretically and practically by extending the application of constructivist, cognitive multimedia, and motivational (ARCS) frameworks into Islamic education contexts, while also offering empirical evidence that gamified learning can enhance not only academic achievement but also student engagement and skill development. Practically, it provides insights for educators and policymakers in designing interactive, student-centered learning environments through accessible digital platforms.